Ecofriendly preparation of graphene sheets decorated with an ethylenediamine copper(ii) complex composite modified electrode for the selective detection of hydroquinone in water. Issue 2 (12th January 2018) - Sakthinathan, Subramanian; Kokulnathan, Thangavelu; Chen, Shen-Ming; Karthik, Raj; Chiu, Te-Wei
Abstract : A reduced graphene oxide decorated copper(ii ) ethylenediamine complex composite modified electrode was applied for the electrochemical determination of hydroquinone. Abstract : In the present work, we have prepared an ecofriendly reduced graphene oxide decorated copper(ii ) ethylenediamine complex ([Cu(en)2 ] 2+ ) (en = ethylenediamine) modified glassy carbon electrode (GCE) for the electrochemical detection of hydroquinone (HQ). The as-prepared composite was characterized by SEM, EDX, XRD, UV and FT-IR. Moreover, the electrochemical behaviour of the modified electrode was investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV). In addition, the GCE/RGO/[Cu(en)2 ] 2+ modified electrode has excellent electrocatalytic activity towards the detection of HQ. Under the optimized conditions, the proposed sensor exhibited a wide linear detection response range of 0.1 μM–104 μM with a limit of detection of 0.025 μM and a sensitivity of 5.0763 μA μM −1 cm −2 . Furthermore, the fabricated electrode exhibited acceptable reproducibility, repeatability and stability. On the other hand, the GCE/RGO/[Cu(en)2 ] 2+ modified electrodes have been applied for the real sample analysis in environmental water samples, which exhibit acceptable recovery. Hence, it is suggested that the GCE/RGO/[Cu(en)2 ] 2+ modified electrode is a potential electrode material that can be used for the detection of HQ in different real samples.